Production Of Protein Hydrolysates From Soy Okara By Rhizopus Oligosporus - Sulaiman, Ummi Syakina (Pusat Pengajian Teknologi Industri, 2020)
Okara is the solid non-soluble fraction obtained during tofu or soymilk production processes. It is rich in protein is produced in large quantity annually poses a significant disposal problem and its high moisture content cause it susceptible to microbial spoilage. It is usually disposed of as a waste and poses an environmental problem. Most of the nutrients in okara remain in the insoluble form, decreasing its nutritional value. The objective of this research project was to produce protein hydrolysate from soy okara by means of okara fermentation by Rhizopus oligosporus. The specifics objectives are to determine the proximate composition of fresh okara and to determine the effect of fermentation variables (percentage of inoculum and thickness of substrate) of okara by R. oligosporus on fungal growth and amino acid production. R. oligosporus obtained from tempe was directly used as inoculum for okara solid state fermentation. Okara was cultivated by R. oligosporus with different substrate thickness and percentage of inoculum for 72 hours at 25℃ in a dark room. Sampling was done for every six hours interval for growth analysis using glucosamine and amino acid content by using ninhydrin method. The proximate analysis for fresh okara was determined with moisture content of 84.10%. Based on dry basis, there were 33.09% protein content, 10.66% fat content, 0.60% ash content and 55.65% carbohydrate content of okara. Statistically, there was no significant difference of substrate thickness (1 cm or 3 cm) with 2.5% and 5% inoculum on glucosamine and amino acid content. The maximum glucosamine content was 0.203 mg at 2.5% inoculum and 0.208 mg at 5% inoculum while amino acid content was 85.4 µg at 2.5% inoculum and 94.5 µg at 5% inoculum.